PWE-374 Is ct colonoscopy ready for prime time as first line investigation for high risk patients?. (22nd June 2015) - Skouras, T; Bennett, B; Fiske, J; Bassi, A
Abstract : Introduction: With CT virtual colonoscopy (CTVC) emerging as a widely available sensitive tool in the investigation of GI pathology, we changed our practice, and are now investigating patients presenting in our "one stop – 2 week rule" gastroenterology clinic with lower GI symptoms with a flexible sigmoidoscopy followed by a CTVC on the same day. We analysed the diagnostic yield of such an approach in our population. Method: CTVCs of all patients referred to the gastroenterology clinic on a "2-week-rule", within a 5-month period were retrospectively reviewed. Intraluminal and extracolonic findings were identified. Extracolonic findings were classified in High Importance Findings (HIF) and Low Importance Findings (LIF) based on their clinical significance. 1 HIFs comprised of: extracolonic malignancy, aortic aneurysms, lymphadenopathy, adrenal adenomas, liver lesions, hydronephrosis, vascular compromise, pelvic masses. LIFs comprised of: benign cysts, gallbladder calculi, fibroids, renal stones, etc. Results: Scans of 195 patients were reviewed. Of those, 75 were male (38.5%); the median age was 64 years. 188 patients had CTVCs, 6 patients had abdominal CT scan with iv contrast, and 1 patient without iv contrast. 8 CTVCs (4.0%) revealed rectal and sigmoid malignancy, 23(11.7%) revealed further polyps leading to 9 additional colonoscopies and 7 flexible sigmoidoscopies. 101 (51.7%) revealed diverticulosis. 5 CTVCs (2.5%) indicated Inflammatory Bowel Disease. At least one extra-colonic finding was reported in 116 scans (59.4%). Extracolonic HIFs were revealed in 27 scans (13.8%), and in 5 (2.5%) extracolonic malignancy was detected. 4 (2.0%) had an abdominal aortic aneurysm, 2 patients (1.0%) significant hydronephrosis. 6 patients (3.1%) had suspicious lung lymph nodes; 2 (1.0%) had large pelvic lesions; 2 (1.0%) had hepatic lesions; 5 (2.5%) had adrenal adenomas. Some of these patients underwent further investigations, others were referred to specialist services, and some underwent significant interventions (laparotomy, AAA repairs, EBUS biopsies etc.) Conclusion: The protocol of CTVC and flexible sigmoidoscopy for first line investigation of high risk patients presenting with lower GI symptoms allowed same day detection and staging for patients with colonic malignancy but also allowed additional detection of extracolonic malignancies/significant pathologies presenting with lower GI symptoms. However the burden of potentially unnecessary investigations and added patient stress from extracolonic findings of variable significance needs to be taken into consideration. Disclosure of interest: None Declared. Reference: Hara, Amy K. Extracolonic findings at CT colonography. Seminars in Ul/S, CT and MRI. 26(1), WB Saunders, 2005